Author Correction: A novel perspective on MOL-PCR optimization and MAGPIX analysis of in-house multiplex foodborne pathogens detection assay - Reslova, Nikol; Huvarova, Veronika; Hrdy, Jakub; Kasny, Martin; Kralik, Petr (Scientific reports, 2019)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.